COMPARATIVE OF FIRST LINE MEDICATIONS FOR PRIMARY OPEN ANGLE GLAUCOMA : A SYSTEMATIC REVIEW - Rahmad, Denie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Glaucoma is the second leading cause of blindness globally, of which primary open-angle glaucoma (POAG) is the most common type, and its prevalence is estimated at 2 worldwide. The prevalence of glaucoma contributes to significant medical costs, and the majority of costs are medication related. Most medications used in the management of glaucoma are targeted at decreasing intraocular pressure (IOP), with each millimeter of mercury (mm Hg) IOP reduction shown to reduce the risk of glaucoma progression and subsequent vision loss by 10. The aim: This study aims to show the comparative of first line medications for primary open angle glaucoma. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search on SagePub brought up 124 articles. The results of the search conducted for the last year of 2013 yielded a total 12 articles for PubMed and 34 articles for SagePub. The result from title screening, a total 10 articles for PubMed and 12 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: All active first-line drugs are among the most efficacious drugs, although the within class differences were small and may not be clinically meaningful. All factors, including adverse effects, patient preferences, and cost should be considered in selecting a drug for a given patient.